The Effect of Compost Variation in Engineered Soil Media on Hydraulic and Hydrologic Performance - Soil Column Study - Mohd Razali, Nawal Nadia Nabilla (Universiti Teknologi PETRONAS, 2017)
Bioretention system is one of the stormwater best management practice (BMP) that utilize vegetation plant, mixtures of medium soil, medium sand and also compost to filter stormwater runoff and to reduce peak runoff flow rate. However, presence of compost in the soil mixture will give variation to the soil characteristic such as the permeability, porosity and the hydraulic conductivity that eventually will affect the hydraulic and hydrologic performance. This study is conducted to investigate the effect of compost variation used in engineered soil media on hydraulic and hydrologic performance of bioretention system. Analysis on the effect of compost variation in the soil mixture used on hydraulic and hydrologic performance have been done by using soil column study approach. Seven (7) soil columns been set up and being monitored in six (6) weeks time. Two (2) types of composts are been used which are organic and rabbit’s manure compost. In addition, each of the soil mixtures with compost used in the system being planted with hibiscus plant and ixora plant.